Five overlooked dimensions of campus wellness: Qualitative lessons from a Health Sciences Center's wellness program evaluation. - Khorsandi, Nikka; Embley, Scott; Bishop-Baier, Margaret (Journal of American College Health)
Objective: Successful university wellness programs approach wellness holistically and regularly assess for improvements to program offerings. This case-study reports five lessons learned from a university wellness program evaluation that must be considered when developing wellness programming. Participants: Faculty, staff, and students at a public university health sciences center. Methods: A 23-question electronic survey with open-ended questions was administered to measure feedback on current and future wellness programming. Responses were analyzed with an open coding approach into five themes for program improvement to more holistically address wellness. Results: The five improvements to wellness programming identified by respondents were: wellness offering awareness, workplace culture and environment, racial representation, wellness programming policy enforcement, and creating an environmentally friendly campus. Conclusions: Themes identified in this case-study require additional attention by university wellness programs to ensure they are equitably accessible and comprehensive in their offerings.